2018
DOI: 10.1364/ol.43.001243
|View full text |Cite
|
Sign up to set email alerts
|

Compact sub-kilohertz low-frequency quantum light source based on four-wave mixing in cesium vapor

Abstract: Using a nondegenerate four-wave mixing (FWM) process based on a double-Λ scheme in hot cesium vapor, we demonstrate a compact diode-laser-pumped quantum light source for the generation of quantum correlated twin beams with a maximum squeezing of 6.5 dB. The squeezing is observed at a Fourier frequency in the audio band down to 0.7 kHz which, to the best of our knowledge, is the first observation of sub-kilohertz intensity-difference squeezing in an atomic system so far. A phase-matching condition is also inves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“…We believe that with the present 4WM scheme a single-frame image with an approximately 1 microsecond long pulse of light onto a CCD camera could provide sub-shot-noise intensity-difference imaging. In the seeded 4WM process the small phase-matching angle (≈ 0.1 • to 0.2 • in potassium vapor [20,21]; ≈ 0.3 • to 0.5 • in rubidium vapor [10,22,23]; ≈ 0.3 • in cesium vapor [24]) limits the high spatial frequency parts of the twin images when being reimaged when we use the imaging setup (Fig. 2 (b)).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that with the present 4WM scheme a single-frame image with an approximately 1 microsecond long pulse of light onto a CCD camera could provide sub-shot-noise intensity-difference imaging. In the seeded 4WM process the small phase-matching angle (≈ 0.1 • to 0.2 • in potassium vapor [20,21]; ≈ 0.3 • to 0.5 • in rubidium vapor [10,22,23]; ≈ 0.3 • in cesium vapor [24]) limits the high spatial frequency parts of the twin images when being reimaged when we use the imaging setup (Fig. 2 (b)).…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments have reported twin-beam intensitydifference squeezing from 4WM down into the kHz range [16,25,26]. Very recently Ma et al [17] reported such squeezing down to frequencies below 700 Hz. In the context of imaging, Kumar et al [27] performed intensity-differencing on an EM-CCD camera using a 4WM source similar to ours and were able to obtain a subtraction noise level 2 dB below shot noise.…”
Section: Introductionmentioning
confidence: 94%
“…Single-mode quadrature squeezing has perhaps its most important applications in future gravity-wave interferometers [12][13][14], and such squeezing at frequencies as low as 1 Hz has been observed from an optical parametric oscillator (OPO) with this application in mind [14,15]. Squeezing has not been reported at such low frequencies for two-mode intensity-difference measurements, and the best results seem to be ≈ 1.5 kHz reported in [16], and ≈ 700 Hz recently reported in [17].…”
Section: Introductionmentioning
confidence: 99%
“…Turnbull et al studied a range of angles for a proper phase matching condition to obtain high gain on a typical 4WM process [12]. The quantum correlations in a 4WM is drastically reduced for smaller angles between the probe and conjugate beams, and it was shown that below 2 mrads the intensity difference squeezing is lost [13].…”
mentioning
confidence: 99%